Strain Serratia sp. S119: A potential biofertilizer for peanut and maize and a model bacterium to study phosphate solubilization mechanisms - Ludueña, Liliana Mercedes (2018)
Strain Serratia sp. S119 is a peanut native bacterium with high phosphate solubilizing activity that promotes the growth of peanut and maize in the cultivation area of Córdoba in Argentina. The aims of this study were to obtain and analyze the genome sequence of Serratia sp. S119 to understand the genetic basis of its beneficial properties on plant growth, and to demonstrate phosphate solubilizing ability in early stages of bacterial growth. Results obtained indicated that soluble P and gluconic acid were detected during exponential growth phase in bacterial supernatant. Analysis of the genome sequence of Serratia sp. S119 obtained from this study showed the presence of genes related to several plant growth promoting traits. The genome sequence of this strain is a valuable source of information to study bacterial response to phosphate starvation and to investigate interaction between this bacterium with host plants under nutritional deficient environments.